2018
DOI: 10.1111/pedi.12792
|View full text |Cite|
|
Sign up to set email alerts
|

Optimal predictive low glucose management settings during physical exercise in adolescents with type 1 diabetes

Abstract: Objectives To assess the optimal setting of the predictive low glucose management (PLGM) algorithm for preventing exercise‐induced hypoglycemia in adolescents with type 1 diabetes. Methods Thirty‐four adolescents, 15 to 20 years, wearing PLGM system, were followed during 3 days exercise during a diabetes camp. PLGM threshold was set at 70 mg/dL between 8 am and 10 pm and 90 mg/dL during 10 pm and 8 am Adolescents were divided into group A and B, with PLGM threshold at 90 and 70 mg/dL, respectively, during exer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 16 publications
(32 reference statements)
0
2
0
2
Order By: Relevance
“…Trata-se de uma revisão integrativa de literatura, que consiste em vários estudos científicos ampliados e completos na área de saúde. O tipo de estudo qualitativo e descritivo, realizado através de materiais científicos indexados nas pesquisas acadêmicas de saúde, nos diversos periódicos nacionais e internacionais (CHERUBINI et al, 2019).…”
Section: Metodologiaunclassified
See 1 more Smart Citation
“…Trata-se de uma revisão integrativa de literatura, que consiste em vários estudos científicos ampliados e completos na área de saúde. O tipo de estudo qualitativo e descritivo, realizado através de materiais científicos indexados nas pesquisas acadêmicas de saúde, nos diversos periódicos nacionais e internacionais (CHERUBINI et al, 2019).…”
Section: Metodologiaunclassified
“…intervenção em: Nível I -revisão sistemática ou metanálise; Nível II -estudos controlados e aleatórios; Nível III -estudos controlados sem randomização; Nível IV -estudos caso-controle ou de coorte; Nível V -revisão sistemática de estudos qualitativos ou descritivos; Nível VIestudos qualitativos ou descritivos e Nível VII -opiniões ou consensos(CHERUBINI et al, 2019). Os artigos selecionados para o estudo, apresenta as devidas recomendações do PRISMA, representado na Figura 1.…”
unclassified
“…Published evidence has indicated that SAPs are associated with reduced moderate and severe hypoglycemia compared with MDI and reduced severe hypoglycemia compared with CSII, as well as improved blood glucose levels and glycemic variability versus sensor-augmented MDI therapy, while SIPs have been associated with a significantly reduced time spent in hypoglycemia and substantially fewer non-severe and severe hypoglycemic events compared with CSII in individuals with T1D with a high risk of hypoglycemia [37][38][39]. SIPs have also been associated with effective prevention of exerciseinduced hypoglycemia [40,41].…”
Section: Sensor-augmented and Sensor-integrated Pumpsmentioning
confidence: 99%
“…The Diabetes Poland clinical guidelines define the principles of determining the eligibility of people living with type 1 diabetes for practising sports, with consideration of professional and extreme sports. In line with the Diabetes Poland position, the use of CGM systems is recommended while practising high-risk sport disciplines [33][34][35][36][37][38][39][40][41][42][43][44].…”
Section: Importance Of Technologies Based On Real-time Continuous Glu...mentioning
confidence: 99%